1979
DOI: 10.1111/j.1365-2133.1979.tb05642.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dicarboxylic acids on normal human melanocytes in dispersed tissue culture*

Abstract: Since dicarboxylic acids are competitive inhibitors of tyrosinase, and effective in treatment of hyperpigmentary disorders, such as chloasma and lentigo maligna, probably due to a cytotoxic effect on abnormal melanocytes, it is of interest to examine their effect on normal melanocytes in tissue culture. Azelaic or dodecandioic acids were added (150-200 micrograms/ml) to dispersed cultures of epidermal cells, and melanocytes were examined by electron microscopy after 7, 10, 15, 20 and 30 days. Apart from a stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…A functional, i.e. Clearly, differences in technique can influence results in tissue culture carried out in different laboratories, and Schachtschabel's observation is important in demonstrating an inhibitory effect of azelaic acid on melanoma cells in culture at concentrations which can, in fact, be effectively achieved by topical application of a 20",, cream to lesions of melasma and lentigo mahgna, with positive effect (Nazzaro-Porro et al, 1979. Schachtschabel (1984) has shown that concentrations of 1-3 X 10" ^ M azelaic acid significantly inhibit growth of Harding-Passey melanoma cells cultured with serum-free media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A functional, i.e. Clearly, differences in technique can influence results in tissue culture carried out in different laboratories, and Schachtschabel's observation is important in demonstrating an inhibitory effect of azelaic acid on melanoma cells in culture at concentrations which can, in fact, be effectively achieved by topical application of a 20",, cream to lesions of melasma and lentigo mahgna, with positive effect (Nazzaro-Porro et al, 1979. Schachtschabel (1984) has shown that concentrations of 1-3 X 10" ^ M azelaic acid significantly inhibit growth of Harding-Passey melanoma cells cultured with serum-free media.…”
Section: Discussionmentioning
confidence: 99%
“…This difference in reactivity between normal and abnormal cells appeared to be borne out by the demonstration that melanocytes in mixed cultures of epidermal cells were not damaged ultrastructurally by exposure to azelaic or dodecanedioic acids at a concentration of 10 ^ M (Breathnach et aL, 1979). This difference in reactivity between normal and abnormal cells appeared to be borne out by the demonstration that melanocytes in mixed cultures of epidermal cells were not damaged ultrastructurally by exposure to azelaic or dodecanedioic acids at a concentration of 10 ^ M (Breathnach et aL, 1979).…”
mentioning
confidence: 99%
“…On 13 December 1979 the lesion had increased greatly in size. Exenteration refused: Reviewed until 11 September 1980, when course of azelaic acid started. After 1 month her creatinine kinase was elevated and she became hypokalaemic.…”
Section: Methodsmentioning
confidence: 99%
“…It was first described by Nazzaro-Porro and Passi [7 ]in the 1970s, and its effectiveness was first observed in hyperpigmentation. This finding was followed by evidence of its efficacy in acne vulgaris [8,9]. The mechanism of action of AzA against acne includes at least three described pharmacological effects: an anti-inflammatory effect, a stabilizing effect on the differentiation of keratinocytes in the follicular infundibulum, and an antimicrobial effect on various microorganisms including P. acnes and Staphylococcus epidermidis .…”
Section: Introductionmentioning
confidence: 99%